2021
DOI: 10.3390/molecules26113387
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling, Toxicity and Anti-Inflammatory Activities of Essential Oils from Three Grapefruit Cultivars from KwaZulu-Natal in South Africa

Abstract: The medicinal potential and volatile composition of different parts of three cultivars of grapefruit (Citrus paradisi) were evaluated for their toxicity and anti-inflammatory activities. Fresh leaf and fruit peel were separately isolated by hydrodistillation for 4 h. The essential oils were subjected to GC/GC-MS analysis for chemical profile. Toxicity of the essential oils in mice were evaluated using Lorke’s method, while an anti-inflammatory assay was performed in a rat model using egg albumin-induced oedema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…The anti-inflammation activity of Fr-GEO and Fr-GEO_SD seen in the present study may be a result of a complex interaction among their various chemical compounds, which might produce synergistic or additive effects, even for those present at low concentrations. Also, we do not exclude the possibility that such effects may be linked to the known antioxidant potential of grapefruit (Miya et al, 2021), which has not been tested in the present study. In addition, the anti-inflammatory activities of EOs are often related to their analgesic properties (de Cassia da Silveira e Sa et al, 2013), which further support their use in health care, but also the potential clinical significance of our findings.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The anti-inflammation activity of Fr-GEO and Fr-GEO_SD seen in the present study may be a result of a complex interaction among their various chemical compounds, which might produce synergistic or additive effects, even for those present at low concentrations. Also, we do not exclude the possibility that such effects may be linked to the known antioxidant potential of grapefruit (Miya et al, 2021), which has not been tested in the present study. In addition, the anti-inflammatory activities of EOs are often related to their analgesic properties (de Cassia da Silveira e Sa et al, 2013), which further support their use in health care, but also the potential clinical significance of our findings.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, in an in vitro study where the cells were treated with volatile compounds of orange juice (Held et al., 2007), the authors found that α‐terpineol effectively inhibited IL‐6, while limonene showed a stimulating effect on IL‐6 production. Further, it has been reported that phellandrene was the dominating compound in the leaf oils of three varieties of C. paradisi from South Africa (“Rose Pink,” “Ruby Red,” and “White Marsh”) (Miya et al., 2021). The same authors also observed the anti‐inflammatory potential of the oils, among which the “Rose Pink” peel oils had the highest and fastest efficacy (reducing inflammation within the first 2 h compared to those after the third and fourth hours with other color variants “White Marsh” and “Ruby Red,” respectively) (Miya et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two major volatile compounds were selected for multivariate statistical analysis, among which d-limonene was the highest relative content (Table S5) and the most abundant ingredient in other citrus peel, such as bergamot (Citrus bergamia (Rutaceae)), lemon (Citrus limon (Rutaceae)), and grapefruit (C. paradisi (Rutaceae)). (Gioffrè et al, 2020;Miya et al, 2021;Verzera et al, 2001). The reported literature has illustrated that the γ-terpinene is lower in grapefruit peel (about 0.1%), but it is higher in the oriental mandarin cultivars peel (Owari and Okitsu), ranging from 3.6% to 4.1% (Merle et al, 2004).…”
Section: Multivariate Statistical Analysis Of Main Volatile Compounds In Crcp During Storagementioning
confidence: 99%
“…Resultados del análisis organoléptico y fisicoquímico preliminar se presentan en la tabla 1. El rendimiento del AE de Citrus paradisi de 0,15% (V/P) es similar al reportado por Villa 19 , pero menor al reportado por Miya et al, que oscilan entre 0,34-0.57 % 20 . El rendimiento del aceite esencial de hojas de Schinus molle de 1,1%, fue mayor que los reportados en otros estudios, que van desde 0.1154 -0,214 % 21,22 .…”
Section: Análisis Preliminar Y Fisicoquímicounclassified
“…El análisis de CG-MS del AE de cáscara de Citrus paradisi, reveló 21 compuestos volátiles (tabla 2), de los que 3 representan 94,61 % (D-Limoneno con 83,45 %, Octanal con 8,68% y beta-mirceno con 2,48 %). Los resultados son similares a otros estudios respecto a la concentración de limoneno (20,24,25), pero difieren en concentración de otros compuesto como alfa-pineno, beta-pineno y linalol 24,25 .…”
Section: Composición Químicaunclassified